Gendered Language on the Economics Job Market Rumors Forum - Alice H. Wu (AEA Papers and Proceedings, 2018)
This paper examines the existence of an unwelcoming or stereotypical culture using evidence on how women and men are portrayed in anonymous discussions on the Economics Job Market Rumors forum (EJMR). I use a Lasso-Logistic model to measure gendered language in EJMR postings, identifying the words that are most strongly associated with discussions about one gender or the other. I find that the words most predictive of a post about a woman are typically about physical appearance or personal information, whereas those most predictive of a post about a man tend to focus on academic or professional characteristics.